On the Harary Index of Γ(Zn) - Gürsoy, Arif; ÜLKER, ALPER; Kircali Gürsoy, Necla (Bayram Sahin, 2024)
In this work, the Harary index of zero-divisor graphs of rings Zn are calculated when n is a member of the set {2p, p2, pλ, pq, p2 q, pqr} where p, q and r are distinct prime numbers and λ is an integer number. We give the formulas for computing the Harary index of Γ(Zn). Moreover, the Harary index of graphs for products of rings were computed. © 2024, Bayram Sahin. All rights reserved.
Keywords: Distance in Graph; Graph Theory; Harary Index; Topological Indeces; Zero-divisor Graph